Big ecology: the emergence of ecosystem science - Coleman, David C (University of California Press, 2010)
In Big Ecology, David C. Coleman documents his historically fruitful ecological collaborations in the early years of studying large ecosystems in the United States. As Coleman explains, the concept of the ecosystem—a local biological community and its interactions with its environment—has given rise to many institutions and research programs, like the National Science Foundation’s program for Long Term Ecological Research. Coleman’s insider account of this important and fascinating trend toward big science takes us from the paradigm of collaborative interdisciplinary research, starting with the International Geophysical Year (IGY) of 1957, through the International Biological Program (IBP) of the late 1960s and early 1970s, to the Long-Term Ecological Research (LTER) programs of the 1980s.